Arguing with numbers : the intersections of rhetoric and mathematics - Wynn, James, 1972-; Reyes, G. Mitchell (RSA series in transdisciplinary rhetoric., 2021)
"A collection of essays which deploy rhetorical lenses to explore how mathematics influences the values and beliefs with which we assess the world and make decisions, as well as how our values and beliefs influence the kinds of mathematical instruments we construct and accept"--